The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2147/prbm.s319379
|View full text |Cite
|
Sign up to set email alerts
|

Trait Anxiety and Social Media Fatigue: Fear of Missing Out as a Mediator

Abstract: Background Interdisciplinary literature indicates different correlates of social media fatigue (hereinafter: SMF). Some studies show that high levels of anxiety may induce lowered Internet use and lead social media users to withdraw from Internet activities. Since the relationship between anxiety and social media use is complex, it is important to investigate mediating factors that may indirectly contribute to or exacerbate this association. Therefore, the main aim of this study is to verify wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…In order to detect multicollinearity, the Variance Inflation Factor (VIF) and tolerance values were applied [114]. Following the general rule, it was assumed that the VIF values should not exceed 5.0 [115] and tolerance values should not be less than 0.1 [116]. The Mahalanobis distance with the criterion of p < 0.001 and Cook's distance with case values lower than 1 were implemented to verify the presence of outliers.…”
Section: Discussionmentioning
confidence: 99%
“…In order to detect multicollinearity, the Variance Inflation Factor (VIF) and tolerance values were applied [114]. Following the general rule, it was assumed that the VIF values should not exceed 5.0 [115] and tolerance values should not be less than 0.1 [116]. The Mahalanobis distance with the criterion of p < 0.001 and Cook's distance with case values lower than 1 were implemented to verify the presence of outliers.…”
Section: Discussionmentioning
confidence: 99%
“…However, an analysis of the individual item factor loadings indicated that there was still an item (i.e., 10) with a factor loading below 0.6 on the single factor. This can also be theoretically justified in that the fear of missing out is considered a type of social anxiety (Li et al, 2022), and high levels of anxiety can lead social media users to withdraw from Internet activities (Swiatek et al, 2021). Therefore, this item is related to the antecedent of PSW and was removed from the item pool to improve the reliability of the measurement instrument, thus reducing the instrument to six items.…”
Section: Pilot Testmentioning
confidence: 99%
“…Women with generalized anxiety disorder (GAD) report greater fatigue than healthy women [24]. Individuals with higher trait anxiety have stronger social media fatigue (SMF) in terms of cognition, behavior, and emotion [25]. Chronic stress is related to anxiety and depression, and anxiety and depression can affect fatigue.…”
Section: Mediating Role Of Depression and Anxietymentioning
confidence: 99%